A promiscuous glycosyltransferase generates poly-β-1, 4-glucan derivatives that facilitate mass spectrometry-based detection of cellulolytic enzymes. Issue 25 (8th June 2021) - Bulmer, Gregory S.; Mattey, Ashley P.; Parmeggiani, Fabio; Williams, Ryan; Ledru, Helene; Marchesi, Andrea; Seibt, Lisa S.; Both, Peter; Huang, Kun; Galan, M. Carmen; Flitsch, Sabine L.; Green, Anthony P.; et al.
Abstract : Promiscuous activity of a glycosyltransferase was exploited to polymerise glucose from UDP-glucose via the generation of β-1, 4-glycosidic linkages. Abstract : Promiscuous activity of a glycosyltransferase was exploited to polymerise glucose from UDP-glucose via the generation of β-1, 4-glycosidic linkages. The biocatalyst was incorporated into biocatalytic cascades and chemo-enzymatic strategies to synthesise cello-oligosaccharides with tailored functionalities on a scale suitable for employment in mass spectrometry-based assays. The resulting glycan structures enabled reporting of the activity and selectivity of celluloltic enzymes.